On the question of pluralism within the meaning of the concept of «advocacy» and its comparison to the term «lawyer» - Заборовський, Віктор Вікторович (Problems of legality, 2016)
The article is devoted to the various perspectives on the definition of the concept of «advocacy». Based on the analysis concluded, according to which Ukrainian lawmakers form a legal definition of «advocacy» should take into account that it must play all its essential features. In our view, such a definition should include a reference to the fact that the bar is an institution of civil society is independent and independent human rights institution in the mechanism of justice and consideration, especially in a professional association of people (lawyers), which aims to ensure proper implementation of the constitutional obligation to provide professional legal (legal) assistance. Expands to value the concepts of «advocacy» and «lawyer», based primarily on the fact that it should be perceived not only as a simple ratio of the constituent elements (advocates) and whole (the Bar), which refers to the legal profession as a professional organization (association) lawyers . We believe that analyzing the correlation of these concepts must proceed from the fact that they are essentially different functions (basic function of a lawyer – is to provide professional legal assistance to clients, while the main function of advocacy – to create conditions for the effective provision of such aid lawyers) but are linked and have a reciprocal influence on each other.